2017
DOI: 10.1590/2177-6709.22.2.035-044.oar
|View full text |Cite
|
Sign up to set email alerts
|

Retention period after treatment of posterior crossbite with maxillary expansion: a systematic review

Abstract: OBJECTIVE: The aim of this systematic review was to evaluate the duration of the retention period in growing patients undergoing maxillary expansion and its relation with posterior crossbite stability. METHODS: Search strategies were executed for electronic databases Cochrane Library, Web of Science, PubMed and Scopus, which were completed on January 15, 2016. The inclusion criteria included randomized, prospective or retrospective controlled trials in growing subjects with posterior crossbite; treated with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…3 To minimize the potential for relapse, a long retention period of 3-6 months is recommended to allow sufficient time for the restoration of bone mineral density (BMD) within the expanded suture. 4,5 To shorten the retention period and obtain ideal RME treatment effects in patients with constricted maxillary arches, additional strategies are required to increase bone formation in the suture. 1,2,4,5 Bone formation is known to be more active in the midpalatal suture after application of an expansion force, compared with sutures without any intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 To minimize the potential for relapse, a long retention period of 3-6 months is recommended to allow sufficient time for the restoration of bone mineral density (BMD) within the expanded suture. 4,5 To shorten the retention period and obtain ideal RME treatment effects in patients with constricted maxillary arches, additional strategies are required to increase bone formation in the suture. 1,2,4,5 Bone formation is known to be more active in the midpalatal suture after application of an expansion force, compared with sutures without any intervention.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 To shorten the retention period and obtain ideal RME treatment effects in patients with constricted maxillary arches, additional strategies are required to increase bone formation in the suture. 1,2,4,5 Bone formation is known to be more active in the midpalatal suture after application of an expansion force, compared with sutures without any intervention. [6][7][8] Previous reports have shown that bone morphogenic protein 2 (BMP-2) can promote bone formation in the expanded suture and decrease the relapse ratio.…”
Section: Introductionmentioning
confidence: 99%
“…However, this was done by retrieving evidence through systematic reviews. 5,6 Few documents analyze the use and importance of produced information and the relationships among research projects on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Bei zahngetragenen Geräten wird in der Literatur oft eine geringfügige Überexpansion empfohlen. Die Kronen der Oberkiefer-zähne werden während der Erweiterung etwas nach bukkal gekippt und richten sich nach Erweiterung wieder auf [7,8].…”
unclassified
“…Damit ist man im ersten halben Jahr unabhängig von der Patientenmitarbeit. Die häufigsten Rezidivraten sieht man bei Compliance-abhängigen, herausnehmbaren Retentionsgeräten [7] (▶Abb. 1-4).…”
unclassified